Organic-inorganic composite electrothermal film material and preparation method and application thereof
By pouring an electric heating layer of low-melting glass powder and conductive filler on the polyimide fiber framework, the problem of difficulty in using carbon-based electric heating materials in high-temperature environments is solved, and the high-temperature stability and mechanical properties are improved, suitable for high-temperature Electric heating applications.
Patent Information
- Application Number
- CN202411552410.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2024-12-31
AI Technical Summary
There are difficulties in safe use of existing carbon-based electrothermal materials in environments with high temperature range (>200℃), insufficient heating temperature and poor mechanical stability, which limits their application in the field of high temperature.
The organic and inorganic composite electrothermal film material consisting of polyimide fiber skeleton, low-melting glass powder, conductive fillers and liquid dispersants are prepared by electrospinning to form an electrothermal layer with high temperature resistance and polyimide An electric heating layer is poured on the fiber skeleton and counter electrodes are arranged to achieve tight connections.
It realizes high-temperature resistance characteristics of heating to 350℃ in a short time and working at a high temperature of 200~300℃ for a long time. It has a flame retardant, excellent mechanical properties, long service life, high safety, low cost and easy operation. Material.
Smart Images

Figure CN119233453A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electric heating materials, and in particular to an organic-inorganic composite electric heating film material and a preparation method and application thereof. Background Art
[0002] With the rapid development of modern science and technology, the requirements for home physiotherapy and health care heating, industrial product thermal processing and heat treatment conditions are becoming more and more stringent. The development and research of heating methods and new heating materials occupy an extremely important position in the fields of material science and energy development. With the deepening of research, the types of electric heating materials are becoming more and more abundant, and their application range is also becoming more and more extensive.
[0003] At present, common electric heating materials include metal electric heating materials, ceramic electric heating materials and carbon-based electric heating materials. Metal-based electric heating materials have the advantages of fast thermal conductivity and rapid heating, but they have the disadvantages of high electric heating efficiency, low cost and easy corrosion. Ceramic-type electric heating materials have the advantages of high electric heating conversion efficiency, strong oxidation resistance and corrosion resistance, but they have the disadvantages of slow temperature rise response and poor toughness. In order to overcome the shortcomings of metal and ceramic electric heating materials, carbon-based electric heating materials have been developed successively, which has promoted the development of electric heating materials to a certain extent. Conductive carbon materials have attracted much attention due to their high conductivity, environmental friendliness, low cost, good stability and many other advantages. In particular, the use of flexible and well-formed polymers as the substrate, the composite of conductive carbon fillers and polymers to make carbon-based polymer composite electric heating film materials has become a hot spot in the field of electric heating composite materials.
[0004] For example, in patent CN108521683B, ultrasonically dispersed graphene, graphene oxide and nanocellulose composite slurry are spray-printed on a substrate and cured to form an electric heating layer. Nevertheless, the heating temperature of such electric heating composite materials is less than 100°C, and the mechanical stability is poor, which greatly limits its application in high-temperature fields. Therefore, how to break through the safe use of carbon-based electric heating materials in high-temperature environments (>200°C) is still a difficult problem that needs to be solved urgently. Summary of the invention
[0005] The purpose of the present invention is to solve the problems existing in the prior art and provide an organic-inorganic composite electric heating film material and a preparation method and application thereof. The electric heating film material is an organic-inorganic composite material with high temperature resistance. It can be heated to 350°C in a short time and can work stably for a long time at a high temperature of 200-300°C.
[0006] The technical solution adopted by the present invention to solve its technical problem is: In a first aspect, the present invention provides an organic-inorganic composite electric heating film material, comprising a polyimide fiber skeleton, an electric heating layer cast on the skeleton to form a film, and a counter electrode arranged on the electric heating layer; the polyimide fiber skeleton is prepared by electrospinning; the counter electrode and the electric heating layer are connected by curing.
[0007] As a further improvement of the present invention, the fiber diameter in the polyimide fiber skeleton is 10~1000 nm.
[0008] As a further improvement of the present invention, the electric heating layer material is composed of the following substances in parts by weight: 60-80 parts of low-melting-point glass powder, 20-40 parts of conductive filler and 100-300 parts of liquid dispersant.
[0009] As a further improvement of the present invention, the low-melting-point glass powder is one or more of Pb-Bi-B, Pb-Zn-B, Pb-Si-B, Bi-Zn-B, VP-Sb, Zn-B-Si or Sn-P-Zn.
[0010] As a further improvement of the present invention, the particle size of the low melting point glass powder is 6-16 μm.
[0011] As a further improvement of the present invention, the conductive filler is one or more of conductive graphite, carbon black, carbon nanotubes, carbon nanofibers, graphene, graphene oxide or activated carbon.
[0012] As a further improvement of the present invention, the liquid dispersant is one or more of dimethylformamide, dimethylacetamide, N-methyl-2-pyrrolidone, isopropanol, n-butanol, ethanol, glycerol or distilled water.
[0013] The second object of the present invention is to provide a method for preparing the inorganic composite electric heating film material according to the above, comprising the following steps: placing a syringe filled with a polyimide solution in an electrospinning device for electrospinning to obtain a polyimide fiber skeleton; Weigh 60-80 parts of low-melting-point glass powder and 20-40 parts of conductive filler according to weight, add them into 100-300 parts of liquid dispersant, and then stir evenly to prepare inorganic composite electrothermal composite ink; The inorganic composite electrothermal composite ink is poured on the polyimide fiber skeleton, dried at 300-350°C for 2-4 hours, and then naturally cooled to form a film to obtain an organic-inorganic composite electrothermal film material. A counter electrode is arranged on the surface of the organic-inorganic composite electric heating film material to obtain an organic-inorganic composite electric heating film.
[0014] As a further improvement of the present invention, the process parameters of the electrospinning are: substrate running speed 0.2~2.0 m / min, drum rotation speed 6~10 rpm, receiving distance 10~50 cm, voltage 15~50 kV, nanofiber weight 10~100 g / m 2 .
[0015] The third object of the present invention is to provide an application of the organic-inorganic composite electric heating film material as a high-temperature electric heating film material, especially for use in fan blades.
[0016] Compared with the prior art, the organic-inorganic composite electric heating film material provided by the present invention has the following beneficial effects: The present invention provides an organic-inorganic composite electric heating film material that is resistant to high temperatures, has strong flame retardancy, has a long service life, has good safety, has excellent mechanical properties, is low in cost, and is easy to operate. The organic-inorganic composite electric heating film comprises a layer of a polyimide fiber skeleton, an electric heating layer cast on the skeleton to form a film, and a counter electrode arranged on the electric heating layer; the polyimide fiber skeleton is prepared by an electrostatic spinning method; the electric heating layer material uses low-melting-point glass powder, conductive filler, and liquid dispersant as raw materials; the counter electrode and the electric heating layer are connected by curing. The inorganic composite electric heating film ink is obtained by uniformly mixing the raw materials in a certain proportion, and the ink is cast on the surface of the polyimide fiber skeleton, dried at 300~400℃ for 2~4 hours, and then naturally cooled to obtain the organic-inorganic composite electric heating film. The specific advantages are as follows: (1) The electric heating film material is an organic-inorganic composite material with high temperature resistance. It can be heated to 350°C in a short time and can work stably for a long time at a high temperature of 200~300°C.
[0017] (2) The electric heating film material uses polyimide with a rigid structure as the skeleton, which forms a large number of hydrogen bonds with the electric heating layer, thereby improving the mechanical properties of the organic-inorganic composite electric heating film material and having higher toughness.
[0018] (3) The inorganic composite electric heating film material provided by the present invention has extremely high flame retardancy, excellent safety, and increased service life.
[0019] (4) The preparation process of the organic-inorganic composite electric heating film material provided by the present invention is simple and safe to operate. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The polyimide fiber prepared by the electrospinning method in Example 1; Figure 2 A plan view of the organic-inorganic composite electric heating film material prepared in Example 1; Figure 3 This is a graph of the electrothermal performance of the organic-inorganic composite electrothermal film material prepared in Example 1. DETAILED DESCRIPTION
[0021] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0022] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0023] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple.
[0024] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0025] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "an", "the" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0026] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also indicate the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass in the embodiment description of the present application can be a mass unit known in the chemical industry such as µg, mg, g, kg, etc.
[0027] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, features defined as "first" and "second" may explicitly or implicitly include one or more of the features.
[0028] One of the purposes of the present invention is to provide an organic-inorganic composite electric heating film material, comprising a layer of a polyimide fiber skeleton, an electric heating layer cast on the skeleton to form a film, and a counter electrode arranged on the electric heating layer; the polyimide fiber skeleton is prepared by an electrostatic spinning method; the electric heating layer material uses low-melting point glass powder, conductive filler and liquid dispersant as raw materials; the counter electrode and the electric heating layer are connected by curing.
[0029] The principle of the present invention is: First, electrospinning can produce nanometer-scale fibers, which not only have a large specific surface area and porosity, but also a large aspect ratio and uniform fiber diameter. Polyimide is a polymer material with a rigid ring structure, and the fiber skeleton prepared by electrospinning has excellent thermal stability and mechanical properties.
[0030] Secondly, as one of the main components of the electric heating layer, low melting point glass powder has a low melting temperature and sealing temperature, and has good heat resistance and chemical stability. Conductive fillers are used to provide the electrical conductivity of the electric heating layer to ensure that the electric heating layer can generate heat evenly and quickly. Liquid dispersants are used to evenly disperse low melting point glass powder and conductive fillers to form a stable electric heating layer material.
[0031] Finally, the solidification connection technology can ensure the tight connection between the electrode and the electric heating layer, avoiding poor contact or falling off during use. Solidification connection can also improve the stability and durability of the entire structure.
[0032] As an example, the high thermal stability and mechanical properties of the polyimide fiber skeleton ensure that the electric heating layer can work stably at high temperatures and is not easily deformed or damaged. The composition of the electric heating layer material enables it to have fast and uniform heating performance, which can meet various heating needs. This makes the material have excellent electric heating performance. Both the polyimide fiber skeleton and the low-melting-point glass powder have excellent insulation properties, which can effectively prevent safety hazards such as leakage and short circuit, and have good insulation and corrosion resistance; the polyimide fiber skeleton also has good corrosion resistance and can work stably in harsh environments.
[0033] Furthermore, the process of preparing polyimide fiber skeleton by electrospinning is simple and rapid, and can prepare high-quality fiber skeleton.
[0034] As an example, the preparation process of the electric heating layer material is also relatively simple, and only low-melting-point glass powder, conductive filler and liquid dispersant need to be evenly mixed.
[0035] The composite structure can be applied to multiple fields such as electric heating devices, temperature control systems, medical equipment, and automobiles to meet the heating needs of different fields. In particular, it can be used as a fan blade. Its excellent performance and simple preparation process make the composite structure highly competitive in the market.
[0036] In summary, the composite structure including the polyimide fiber skeleton, the electric heating layer and the counter electrode provided by the present invention has excellent electric heating performance, good insulation and corrosion resistance, and a simple and efficient preparation process, and has broad application prospects.
[0037] Preferably, the diameter of the polyimide skeleton fiber is 10-1000 nm. For example, it can be 50-500 nm, 100-800 nm, 500-1000 nm, and further can be 10 nm, 50 nm, 100 nm, 150 nm, 200 nm, 250 nm, 350 nm, 450 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, 1000 nm, etc. It can be selected as needed.
[0038] In the above scheme, the diameter selection of the polyimide skeleton fiber has an important influence on the performance of the electric heating layer. When the fiber diameter is in the range of 10~1000 nm, it can ensure that the electric heating layer has good flexibility and mechanical strength. Finer fibers (such as 50~500 nm) can provide a higher surface area, which is beneficial to the heat exchange between the electric heating layer and the surrounding environment and improves the heating efficiency. Thicker fibers (such as 800~1000 nm) may provide better structural support and make the electric heating layer more durable. The specific diameter range to be selected depends on the specific performance and application scenarios required by the electric heating layer.
[0039] Preferably, the electric heating layer material is composed of the following substances in parts by weight: 60-80 parts of low-melting-point glass powder, 20-40 parts of conductive filler and 100-300 parts of liquid dispersant, wherein the sum of the low-melting-point glass powder and the conductive filler is 100 parts.
[0040] Preferably, the low-melting-point glass powder is a solid powder with a melting point of 350-500°C, including one or more glass systems of Pb-Bi-B, Pb-Zn-B, Pb-Si-B, Bi-Zn-B, VP-Sb, Zn-B-Si, and Sn-P-Zn.
[0041] The ratio and type of low-melting-point glass powder and conductive filler are crucial to the conductivity and heating performance of the electric heating layer. As a binder, low-melting-point glass powder can melt and solidify at a lower temperature to form a conductive network. Its melting point is selected in the range of 350~500℃ to ensure that other components of the electric heating layer will not be damaged during the heating process.
[0042] Preferably, the particle size of the low melting point glass powder is 6-16 μm, for example, 6-12 μm, 8-16 μm, 7-14 μm, 6 μm, 8 μm, 10 μm, 11 μm, 12 μm, 14 μm, 16 μm, etc.
[0043] The particle size of the glass powder affects its melting speed and the microstructure after solidification. Finer glass powder (such as 6~12 μm) can provide a larger surface area, which is conducive to full mixing with conductive fillers and liquid dispersants. Coarser glass powder may form larger particles, affecting the uniformity and conductivity of the coating. Therefore, choosing the appropriate particle size range can ensure that the electric heating layer has good conductivity and heating performance.
[0044] Different glass systems have different melting points and chemical properties. Choosing the right glass system can ensure that the electric heating layer remains stable during the heating process. Glass powder with a lower melting point can be melted at a lower temperature, which is beneficial to reduce energy consumption and improve heating efficiency. At the same time, the chemical stability of the glass powder is also important to ensure that the electric heating layer will not fail due to chemical reactions during long-term use.
[0045] Different conductive fillers have different conductivity and stability. Conductive graphite, carbon black, etc. have high conductivity, but may not be easy to disperse. Carbon nanotubes, carbon nanofibers, etc. have higher specific surface area and better dispersibility. New materials such as graphene and graphene oxide have excellent conductivity and mechanical properties. Selecting the appropriate type and content of conductive fillers can optimize the conductivity and heating performance of the electric heating layer.
[0046] Preferably, the conductive filler is one or more of conductive graphite, carbon black, carbon nanotubes, carbon nanofibers, graphene, graphene oxide or activated carbon.
[0047] Conductive fillers provide electrical conductivity, and their type and content affect the resistivity and heating efficiency of the electric heating layer. Liquid dispersants are used to evenly disperse low-melting-point glass powder and conductive fillers in the solution for subsequent coating and curing. Their type and content affect the uniformity and stability of the coating.
[0048] Preferably, the liquid dispersant is one or more of dimethylformamide, dimethylacetamide, N-methyl-2-pyrrolidone, isopropanol, n-butanol, ethanol, glycerol or distilled water.
[0049] The choice of liquid dispersant will affect the uniformity and stability of the coating. Organic solvents (such as dimethylformamide, dimethylacetamide, etc.) can provide good solubility and dispersibility, but may cause environmental pollution. Inorganic solvents (such as distilled water) are more environmentally friendly, but may require higher temperatures and pressures to evaporate the solvent. Therefore, choosing the appropriate type and content of liquid dispersant can ensure that the electric heating layer has good coating performance and curing effect.
[0050] The second object of the present invention is to provide a method for preparing the inorganic composite electric heating film material according to the above, comprising the following steps: (1) Place the syringe containing the polyimide solution in the electrospinning equipment for electrospinning. The process parameters are: substrate running speed 0.2~2.0 m / min, roller rotation speed 6~10 rpm, receiving distance 10~50 cm, voltage 15~50 kV, nanofiber weight 10~100 g / m 2 .
[0051] (2) Weighing 60-80 parts of low melting point glass powder and 20-40 parts of conductive filler according to weight, adding them into 100-300 parts of liquid dispersant, and then stirring evenly to prepare inorganic composite electrothermal ink; (3) pouring the electric heating layer ink prepared in step (2) onto the polyimide fiber skeleton, drying at 300-350° C. for 2-4 h, and then naturally cooling to form a film to obtain an organic-inorganic composite electric heating film material; (4) Arranging a counter electrode on the surface of the organic-inorganic composite electric heating film material in step (3) to obtain an organic-inorganic composite electric heating film.
[0052] The preparation method of the inorganic composite electric heating film material of the present invention is based on the principle that the electrostatic spinning technology uses a high voltage electric field to form a jet of polyimide solution, and stretches and refines the solution under the action of the electric field force, and finally deposits the solution on a receiving device to form a nanofiber film. This technology can prepare a polyimide fiber skeleton with a high specific surface area, good flexibility and mechanical strength. The low melting point glass powder and the conductive filler are evenly dispersed in a liquid dispersant to form an inorganic composite electric heating ink. The low melting point glass powder, as a binder, can melt and solidify at a relatively low temperature to form a conductive network; the conductive filler provides conductivity to ensure that the electric heating film has good heating performance. The electric heating ink is poured on the polyimide fiber skeleton, the solvent in the ink is volatilized by drying, the low melting point glass powder is melted and solidified, and is tightly combined with the conductive filler and the polyimide fiber skeleton to form an organic-inorganic composite electric heating film material. A counter electrode is arranged on the surface of the electric heating film material so that a current loop is formed when power is turned on to generate heat.
[0053] The electric heating film material of the present invention adopts an inorganic composite electric heating ink, which has excellent electrical conductivity and thermal conductivity, can achieve rapid heating at a lower voltage, and improve heating efficiency. The electric heating film material does not produce harmful substances during the heating process, and has low energy consumption, which meets the requirements of energy saving and environmental protection. The polyimide fiber skeleton has good flexibility and mechanical strength, so that the electric heating film material can be applied to surfaces of various complex shapes and is not easily damaged during use. The preparation method of the present invention adopts electrostatic spinning and casting technology, which is simple in process, easy to operate, and can realize the continuous production of electric heating film materials. By adjusting the electrostatic spinning parameters, the composition and proportion of the electric heating ink, etc., the performance of the electric heating film material can be accurately controlled to meet the needs of different application scenarios. The preparation method of the inorganic composite electric heating film material of the present invention has the advantages of efficient heating, energy saving and environmental protection, good flexibility and mechanical strength, simple preparation process, strong controllability and customization, and wide application.
[0054] The technical solution of the present invention is further described in detail below through specific embodiments in conjunction with the accompanying drawings.
[0055] Embodiment 1: An organic-inorganic composite electric heating film material, the specific material composition and steps in implementation are: (1) A polyimide solution with a solid content of 10% was placed in a syringe and placed in an electrospinning device. The process parameters were: substrate speed 0.2 m / min, drum rotation speed 8 rpm, receiving distance 15 cm, voltage 15 kV, nanofiber weight about 10 g / m 2 .
[0056] (2) Weigh 6 g of Pb-Bi-B glass powder and 4 g of carbon black respectively according to their weight, mix them evenly, add them into 10 g of N-methyl-2-pyrrolidone, and then stir them evenly to prepare an inorganic composite electrothermal ink; (3) pouring the inorganic composite electrothermal ink prepared in step (2) onto the polyimide fiber skeleton, drying at 300° C. for 4 h, and then naturally cooling to form a film to obtain an organic-inorganic composite electrothermal film material; (4) Arranging a counter electrode on the surface of the organic-inorganic composite electric heating film material in step (3) to obtain an organic-inorganic composite electric heating film. Figure 2 , which is a plan view of the organic-inorganic composite electric heating film material prepared in Example 1.
[0057] The performance of the materials in the examples and the organic-inorganic composite electric heating film finally prepared were analyzed, and the obtained Figure 1 The polyimide fiber prepared by the electrospinning method in Example 1; Figure 3 This is a graph of the electrothermal performance of the organic-inorganic composite electrothermal film material prepared in Example 1.
[0058] The organic-inorganic composite electric heating film material obtained in this embodiment has a polyimide fiber such as Figure 1 As shown, the diameter of the polyimide fiber is 530 nm; its electrothermal properties are as follows Figure 3 As shown in the figure, when a voltage of 25 V is applied across the organic-inorganic composite electric heating film material, a constant temperature state can be quickly reached within 50 s, and the constant temperature can reach 250°C.
[0059] Embodiment 2: An organic-inorganic composite electric heating film material, the specific material composition and steps in implementation are: (1) A polyimide solution with a solid content of 12% was placed in a syringe and placed in an electrospinning device. The process parameters were: substrate speed 0.8 m / min, drum rotation speed 10 rpm, receiving distance 20 cm, voltage 25 kV, nanofiber weight about 15 g / m 2 .
[0060] (2) Weigh 6.5 g of Pb-Zn-B and Pb-Si-B glass powders and 4 g of conductive graphite according to their weight, mix them evenly, add them into 20 g of n-butanol, and then stir them evenly to prepare an inorganic composite electrothermal ink; (3) pouring the inorganic composite electrothermal ink prepared in step (2) onto the polyimide fiber skeleton, drying at 320° C. for 3 h, and then naturally cooling to form a film to obtain an organic-inorganic composite electrothermal film material; (4) Arranging a counter electrode on the surface of the organic-inorganic composite electric heating film material in step (3) to obtain an organic-inorganic composite electric heating film.
[0061] The organic-inorganic composite electric heating film material obtained in this embodiment has a polyimide fiber diameter of 420 nm. When a voltage of 21 V is applied across the organic-inorganic composite electric heating film material, it can reach a constant temperature state within 50 seconds, with a constant temperature of 280°C, and can work stably for a long time.
[0062] Embodiment 3: An organic-inorganic composite electric heating film material, the specific material composition and steps in implementation are: (1) A polyimide solution with a solid content of 15% was placed in a syringe and placed in an electrospinning device. The process parameters were: substrate speed 1.2 m / min, drum rotation speed 8 rpm, receiving distance 25 cm, voltage 50 kV, nanofiber weight about 16 g / m 2 .
[0063] (2) 8 g of Pb-Bi-B and VP-Sb glass powders, 2 g of graphene and carbon nanotubes were weighed respectively according to their weight proportions, mixed evenly, added into 30 g of dimethylacetamide, and then stirred evenly to prepare an inorganic composite electrothermal ink; (3) pouring the inorganic composite electrothermal ink prepared in step (2) onto the polyimide fiber skeleton, drying at 350° C. for 2.5 h, and then naturally cooling to form a film to obtain an organic-inorganic composite electrothermal film material; (4) Arranging a counter electrode on the surface of the organic-inorganic composite electric heating film material in step (3) to obtain an organic-inorganic composite electric heating film.
[0064] The organic-inorganic composite electric heating film material obtained in this embodiment has a polyimide fiber diameter of 510 nm. When a voltage of 30 V is applied across the organic-inorganic composite electric heating film material, it can quickly reach a constant temperature state within 80 s, and the constant temperature can reach 330°C.
[0065] Embodiment 4: An inorganic composite electric heating film material, the specific material composition and steps are: (1) A polyimide solution with a solid content of 11% was placed in a syringe and placed in an electrospinning device. The process parameters were: substrate speed 1.8 m / min, drum rotation speed 9 rpm, receiving distance 30 cm, voltage 45 kV, nanofiber weight about 10.5 g / m 2 .
[0066] (2) Weigh 7 g of Sn-P-Zn glass powder, 3 g of carbon black and carbon nanofiber according to their weight, mix them evenly, add them into 25 g of distilled water, and then stir them evenly to prepare an inorganic composite electrothermal ink; (3) The inorganic composite electrothermal ink prepared in step (2) is poured onto the polyimide fiber skeleton, dried at 300°C for 3 h, and then naturally cooled to form a film to obtain an organic-inorganic composite electrothermal film material. (4) Arranging a counter electrode on the surface of the organic-inorganic composite electric heating film material in step (3) to obtain an organic-inorganic composite electric heating film.
[0067] The organic-inorganic composite electric heating film material obtained in this embodiment has a polyimide fiber diameter of 350 nm. When a voltage of 45 V is applied across the organic-inorganic composite electric heating film material, a constant temperature state of 300° C. can be reached within 180 s.
[0068] Embodiment 5: An inorganic composite electric heating film material, the specific material composition and steps are: (1) A polyimide solution with a solid content of 13% was placed in a syringe and placed in an electrospinning device. The process parameters were: substrate speed 2.0 m / min, drum rotation speed 10 rpm, receiving distance 50 cm, voltage 50 kV, nanofiber weight about 100 g / m 2 .
[0069] (2) Weigh 8 g of Sn-P-Zn glass powder, 2 g of carbon black and carbon nanofiber according to their weight, mix them evenly, add them into 30 g of distilled water, and then stir them evenly to prepare an inorganic composite electrothermal ink; (3) The inorganic composite electrothermal ink prepared in step (2) is poured onto the polyimide fiber skeleton, dried at 350° C. for 3 h, and then naturally cooled to form a film to obtain an organic-inorganic composite electrothermal film material.
[0070] (4) Arranging a counter electrode on the surface of the organic-inorganic composite electric heating film material in step (3) to obtain an organic-inorganic composite electric heating film.
[0071] The organic-inorganic composite electric heating film material obtained in this embodiment has a polyimide fiber diameter of 500 nm. When a voltage of 45 V is applied across the organic-inorganic composite electric heating film material, a constant temperature state of 310° C. can be reached within 180 s.
[0072] Embodiment 6: An inorganic composite electric heating film material, the specific material composition and steps are: (1) A polyimide solution with a solid content of 14% was placed in a syringe and placed in an electrospinning device. The process parameters were: substrate speed 0.5 m / min, drum rotation speed 6 rpm, receiving distance 10 cm, voltage 15 kV, nanofiber weight about 10 g / m 2 .
[0073] (2) Weigh 6 g of Sn-P-Zn glass powder, 4 g of carbon black and carbon nanofiber according to their weight, mix them evenly, add them into 20 g of distilled water, and then stir them evenly to prepare an inorganic composite electrothermal ink; (3) The inorganic composite electrothermal ink prepared in step (2) is poured onto the polyimide fiber skeleton, dried at 120° C. for 3 h, and then naturally cooled to form a film to obtain an organic-inorganic composite electrothermal film material.
[0074] (4) Arranging a counter electrode on the surface of the organic-inorganic composite electric heating film material in step (3) to obtain an organic-inorganic composite electric heating film.
[0075] The organic-inorganic composite electric heating film material obtained in this embodiment has a polyimide fiber diameter of 800 nm. When a voltage of 45 V is applied across the organic-inorganic composite electric heating film material, a constant temperature state of 280° C. can be reached within 180 s.
[0076] Embodiment 7: An inorganic composite electric heating film material, the specific material composition and steps are: (1) A polyimide solution with a solid content of 14% was placed in a syringe and placed in an electrospinning device. The process parameters were: substrate speed 1.8 m / min, drum rotation speed 8 rpm, receiving distance 35 cm, voltage 35 kV, nanofiber weight about 50 g / m 2 .
[0077] (2) Weigh 6 g of Sn-P-Zn glass powder, 4 g of carbon black and carbon nanofiber according to their weight, mix them evenly, add them into 20 g of distilled water, and then stir them evenly to prepare an inorganic composite electrothermal ink; (3) The inorganic composite electrothermal ink prepared in step (2) is poured onto the polyimide fiber skeleton, dried at 120° C. for 3 h, and then naturally cooled to form a film to obtain an organic-inorganic composite electrothermal film material.
[0078] (4) Arranging a counter electrode on the surface of the organic-inorganic composite electric heating film material in step (3) to obtain an organic-inorganic composite electric heating film.
[0079] The organic-inorganic composite electric heating film material obtained in this embodiment has a polyimide fiber diameter of 1000 nm. When a voltage of 45 V is applied across the organic-inorganic composite electric heating film material, a constant temperature state of 280° C. can be reached within 180 s.
[0080] The third object of the present invention is to provide an application of the organic-inorganic composite electric heating film material as a high-temperature electric heating film material, especially for use in fan blades.
[0081] The above-described embodiments are only preferred solutions of the present invention and are not intended to limit the present invention in any form. Other variations and modifications are possible without exceeding the technical solutions described in the claims.
Claims
1. An organic-inorganic composite electric heating film material, characterized in that: It comprises a polyimide fiber skeleton, an electric heating layer cast on the skeleton to form a film, and a counter electrode arranged on the electric heating layer; the polyimide fiber skeleton is prepared by electrostatic spinning; and the counter electrode and the electric heating layer are connected by curing.
2. The organic-inorganic composite electric heating film material according to claim 1, characterized in that: The fiber diameter in the polyimide fiber skeleton is 10-1000 nm.
3. The organic-inorganic composite electric heating film material according to claim 1, characterized in that: The electric heating layer material is composed of the following substances in parts by weight: 60-80 parts of low-melting-point glass powder, 20-40 parts of conductive filler and 100-300 parts of liquid dispersant.
4. The organic-inorganic composite electric heating film material according to claim 3, characterized in that: The low-melting-point glass powder is one or more of Pb-Bi-B, Pb-Zn-B, Pb-Si-B, Bi-Zn-B, VP-Sb, Zn-B-Si or Sn-P-Zn.
5. The organic-inorganic composite electric heating film material according to claim 3, characterized in that: The particle size of the low-melting-point glass powder is 6-16 μm.
6. The organic-inorganic composite electric heating film material according to claim 3, characterized in that: The conductive filler is one or more of conductive graphite, carbon black, carbon nanotubes, carbon nanofibers, graphene, graphene oxide or activated carbon.
7. The organic-inorganic composite electric heating film material according to claim 3, characterized in that: The liquid dispersant is one or more of dimethylformamide, dimethylacetamide, N-methyl-2-pyrrolidone, isopropanol, n-butanol, ethanol, glycerol or distilled water.
8. A method for preparing the organic-inorganic composite electric heating film material according to any one of claims 1 to 7, characterized in that: The following steps are involved: placing a syringe filled with a polyimide solution in an electrospinning device for electrospinning to obtain a polyimide fiber skeleton; Weigh 60-80 parts of low-melting-point glass powder and 20-40 parts of conductive filler according to weight, add them into 100-300 parts of liquid dispersant, and then stir evenly to prepare inorganic composite electrothermal composite ink; The inorganic composite electrothermal composite ink is poured on the polyimide fiber skeleton, dried at 300-350°C for 2-4 hours, and then naturally cooled to form a film to obtain an organic-inorganic composite electrothermal film material. A counter electrode is arranged on the surface of the organic-inorganic composite electric heating film material to obtain the organic-inorganic composite electric heating film.
9. The method for preparing the organic-inorganic composite electric heating film material according to claim 8, characterized in that: The process parameters of the electrospinning are: substrate running speed 0.2~2.0 m / min, drum rotation speed 6~10 rpm, receiving distance 10~50 cm, voltage 15~50 kV, nanofiber weight 10~100 g / m 2 .
10. A use of the organic-inorganic composite electric heating film material as claimed in any one of claims 1 to 7 as a high-temperature electric heating film material, characterized in that: Used in fan blades.
Citation Information
Cited By
High-thermal-conductivity organic-inorganic composite electrothermal film and preparation method thereof
CN119956560A